FEATURES OF THE SEROLOGICAL DIAGNOSIS OF LISTERIOSIS (LITERATURE REVIEW) - Sagdullayeva G.U. (Scholar Express Journals, 2022)
Listeria are widely distributed in the surrounding ecosystems, from food, environmental objects, circulate in the body and cause disease in animals and humans. In this regard, the close attention that has been drawn to listeriosis infection in the last decade, both in terms of clinical and laboratory diagnostics, is natural. Particularly alarming is the growing role of listeria in perinatal and neonatal pathologies, which are characterized by the severity of the course and high mortality
Keywords: Listeriosis; serovariant; cold chain; L. ivanovi